2022
DOI: 10.1021/acs.iecr.2c01324
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Dye-Sensitized Solar Cells Based on Electrolyte Solutions Containing Choline Chloride/Ethylene Glycol Deep Eutectic Solvent: Electrolyte Optimization

Abstract: Combined experimental and computational analyses were carried out with the aim of developing a cost-effective and sustainable electrolyte solution based on a deep eutectic solvent (DES) for dyesensitized solar cells (DSSCs). A mixture of choline chloride (CholCl, 1 mol) and ethylene glycol (EG, 2 mol) as a DES was used in combination with MeCN, lithium iodide, 1-ethyl-3-methylimidazolium iodide (Emim), and iodine as DSSC electrolytes on TiO 2 and Pt electrodes. It is noteworthy that in this work the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…In a DSSC, the electrolyte is another very important component as it can affect the stability and performance of a cell [75]. The redox couple, organic solvent, and additives are the essential components of an electrolyte.…”
Section: Electrolytesmentioning
confidence: 99%
“…In a DSSC, the electrolyte is another very important component as it can affect the stability and performance of a cell [75]. The redox couple, organic solvent, and additives are the essential components of an electrolyte.…”
Section: Electrolytesmentioning
confidence: 99%
“…24 In another example, M. Isik et al showed the versatility of polyDES chemistry and their applications as sorbents for CO 2 capture. 25 Beyond this, polyDESs have also been investigated as electrolytes, 26,27 as carriers for drug delivery systems, 28 and in coating applications. 29 Our group recently reported the development of DESs based on polyphenols, which showed potential as (bio)adhesives.…”
Section: Introductionmentioning
confidence: 99%